The Cooperation Between The Republic Of Armenia And The Hellenic Republic In The Defence Sphere - Nazaryan, Hayk (NAS RA)
Diplomatic relations between the Republic of Armenia and the Hellenic Republic were established on January 20, 1992. Since the 1990s, strong military-political relations were created between the two Republics. Particularly, the cooperation in the defence sphere includes not only military education and military-technical directions, but also an international peacekeeping mission.
Keywords: Military-technical cooperation